(untitled) (Tempo e Argumento, 2024)
The study of the present time poses an important challenge to the relationship between history and justice, especially in those processes that are still open and in which even official records are not found or are not contained in the truth reports. This paper seeks to reflect on a trajectory of research on forced adoptions in Chile, on the materials, tensions and relationship with justice throughout these years. Our main general questions are: What are the main problems in the access to archives of the past-present? What role do oral sources and memory archives play today? What possibilities and problems are associated with the use of social networks as repositories of testimonies and non-traditional sources? Along with this, we specifically ask ourselves: What are the contributions of the historical discipline in the understanding of forced adoptions in Chile? What challenges does research in this field of study face? With this paper presented in the framework of the V International Seminar on History of the Present Time, we seek to address these questions based on a research trajectory.